2016
DOI: 10.1021/acsinfecdis.5b00136
|View full text |Cite
|
Sign up to set email alerts
|

Identification of “Preferred” Human Kinase Inhibitors for Sleeping Sickness Lead Discovery. Are Some Kinases Better than Others for Inhibitor Repurposing?

Abstract: A kinase-targeting cell-based high-throughput screen (HTS) against Trypanosoma brucei was recently reported, and this screening set included the Published Kinase Inhibitor Set (PKIS). From the PKIS was identified 53 compounds with pEC50 ≥ 6. Utilizing the published data available for the PKIS, a statistical analysis of these active antiparasitic compounds was performed, allowing identification of a set of human kinases having inhibitors that show a high likelihood for blocking T. brucei cellular proliferation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 16 publications
3
38
0
Order By: Relevance
“…Having originally been designed as a multi‐kinase inhibitor, compound 23 has been shown to potently inhibit several members of the human cyclin‐dependent kinase family in addition to human tyrosine kinase EPHA2 . Accordingly, compound 23 was selected as part of a subset of preferred human kinase inhibitors for a target‐repurposing programme to uncover new antitrypanosomal agents . While the specific MOA was not confirmed in this study, 23 displayed potent antitrypanosomal activity.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 93%
“…Having originally been designed as a multi‐kinase inhibitor, compound 23 has been shown to potently inhibit several members of the human cyclin‐dependent kinase family in addition to human tyrosine kinase EPHA2 . Accordingly, compound 23 was selected as part of a subset of preferred human kinase inhibitors for a target‐repurposing programme to uncover new antitrypanosomal agents . While the specific MOA was not confirmed in this study, 23 displayed potent antitrypanosomal activity.…”
Section: Kinetoplastids (Trypanosomiasis and Leishmaniasis)mentioning
confidence: 93%
“…The same authors reported that alvocidib inhibited the growth of L. mexicana mexicana (MNYC/BZ/62/M379) promastigotes in a dose‐dependent manner in vitro. At 1.0 μ m concentration, alvocidib caused a complete arrest of promastigote growth, while a lower concentration resulted in partial growth inhibition . Alvocidib also inhibited the recombinant CRK3his/CYCAhis with an IC 50 of 0.102 μ m , a similar value as compared with IC 50 of 0.1 μ m for Lmx CRK3his .…”
Section: Human Kinase Inhibitor Repurposing In Trypanosomatidsmentioning
confidence: 74%
“…Compounds grouped by similarity of the main human kinase targets are reported in Figures –. Some of them have been indicated as potential T. brucei growth inhibitors according to a statistical analysis driven approach performed on a high throughput screening released by GlaxoSmithKline . In this study, among over 224 human kinases, 29 kinases, defined as Preferred Human Kinases, were statistically selected, and inhibitors of these kinases are indicated to have a better likelihood of activity in the parasite.…”
Section: Human Kinase Inhibitor Repurposing In Trypanosomatidsmentioning
confidence: 99%
See 2 more Smart Citations